2020
DOI: 10.21608/jhiph.2020.111317
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Health Education Program on the Level of Knowledge and Attitude of Pregnant Women Regarding Obstetric Danger Signs in Upper Egypt

Abstract: Background & Objective(s): The present study aimed to assess women's knowledge and attitude towards ODS (obstetric danger signs) among pregnant women in Upper Egypt and improve women's knowledge through the implementation of an educational program. Methods: a quasi-experimental study was conducted among 300 pregnant women attending antenatal clinics. Data collection was done using structured questionnaires which were distributed to the participants during face to face interview with the researchers. An educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(24 reference statements)
0
3
1
Order By: Relevance
“…And in the same line with Mohamed & Hassan [12] , mentioned friends and relatives were the main source of information about dental health care, as mentioned by the studied sample. These results are not in harmony with the findings of Ali et al [14] founded that illustrated that healthcare providers were the main source of information about obstetric danger signs among pregnant women in Upper Egypt.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…And in the same line with Mohamed & Hassan [12] , mentioned friends and relatives were the main source of information about dental health care, as mentioned by the studied sample. These results are not in harmony with the findings of Ali et al [14] founded that illustrated that healthcare providers were the main source of information about obstetric danger signs among pregnant women in Upper Egypt.…”
Section: Discussioncontrasting
confidence: 91%
“…This study is congruence with the study of Abd Elmoniem et al [13] , revealed that more than three fourth of the studied pregnant women had inadequate pre-educational program knowledge, while the majority had good knowledge of post-educational programs. Also, Ali et al [14] , in Upper Egypt, illustrated expectant women's knowledge of obstetrical danger signs increased significantly after the implementation of educational program.…”
Section: Discussionmentioning
confidence: 96%
“…( 21). (Ali et al, 2020) The results of the above article review indicate that providing health education has an impact on pregnant women's knowledge about high-risk pregnancy. This knowledge is a crucial factor in the incidence of high-risk pregnancies since it determines the actions that pregnant women will take in the future.…”
Section: "Effectiveness Of Health Education Program On the Level Of K...mentioning
confidence: 98%
“…Although health seeking behaviours which is influenced by knowledge and attitudes about obstetric danger signs have a tremendous potential to reduce maternal and infant fatalities and morbidities, as well as to improve mothers’ actions toward seeking medical attention, which is essential for safe motherhood (Ali et al, 2020), its status is not well known among this vulnerable population of adolescent pregnant mother especially in Dodoma region which contribute a significant number of adolescent pregnancies in the country…”
Section: Introductionmentioning
confidence: 99%